2012
DOI: 10.7182/pit2012703
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Peripheral Neuropathy after Solid Organ Transplant

Abstract: Development of or worsening of peripheral neuropathy after solid organ transplant may decrease health-related quality of life. Follow-up care should include vigilant monitoring for signs of peripheral neuropathy. Providers need to provide early treatment, education, support, empathy, and understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Those treated with cyclosporin after kidney transplantation have historically reported severe pain, restriction of movement, transient musculoskeletal pain and a leg bone pain syndrome (Collini et al, 2006; Grotz et al, 2001; Prommer, 2012; Smith, 2009). Among liver recipients, severe bodily pain was reported (Hellgren et al, 1998) together with pain in extremities or joints (Rosenblum, Rosen, Pine, Rosen, & Borg‐Stein, 1993) in addition to bone pain and fractures (Textor & Hedrick, 2012). After liver transplantation, 26% of recipients in one study stated that they suffered severe bodily pain (Hellgren et al, 1998), and in another cohort, 18% reported pain in an extremity and 40% had arthralgia (Nicholas, Oleske, Robinson, Switala, & Tarter, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those treated with cyclosporin after kidney transplantation have historically reported severe pain, restriction of movement, transient musculoskeletal pain and a leg bone pain syndrome (Collini et al, 2006; Grotz et al, 2001; Prommer, 2012; Smith, 2009). Among liver recipients, severe bodily pain was reported (Hellgren et al, 1998) together with pain in extremities or joints (Rosenblum, Rosen, Pine, Rosen, & Borg‐Stein, 1993) in addition to bone pain and fractures (Textor & Hedrick, 2012). After liver transplantation, 26% of recipients in one study stated that they suffered severe bodily pain (Hellgren et al, 1998), and in another cohort, 18% reported pain in an extremity and 40% had arthralgia (Nicholas, Oleske, Robinson, Switala, & Tarter, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, deterioration in bone disease led to compression fractures of the vertebrae and pain in the same patient group (Haagsma, Thijn, Post, Sloff, & Gips, 1988). Peripheral neuropathy is an undesirable complication after SOT with unexpected onset, rapid escalation of symptoms, lack of provider monitoring and poor provider response to patient‐reported symptoms (Textor & Hedrick, 2012). The interest in pain among thoracic organ recipients has emerged in the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Besides, it could aid in clinical decisions on the best immunosuppressive regimen helping physicians to choose drugs with less toxicity on the neuromuscular system or to optimize their dosage. 37 39 More generally, our data suggest that all patients with end-stage HF having frequent hospitalizations, independently of being candidates for transplantation, are at risk of developing neuropathy; consequently, in the framework of multidisciplinary outpatient management, it can be important to carry out a neurological follow-up that would allow early identification of neuromuscular disorders and set up a rehabilitation program with improvement in quality of life.…”
Section: Discussionmentioning
confidence: 80%
“…DPN is a chronic condition that may cause symptoms of: hypersensitivity to pain or touch; chronic pain; a tingling, burning or prickling sensation; and numbness (Argoff et al, 2006). These symptoms can negatively impact one's life as the symptoms may be associated with: depression; sleep disturbances; progressive muscle weakness; chronic pain; loss of occupational engagement; balance problems; and decreased quality of life (QoL) (Argoff et al, 2006;Textor and Hedrick, 2012). The growing prevalence of diabetes has significant implications for occupational therapy as occupational therapists play a valuable role in promoting health and preventing chronic disease and disability through participation in meaningful occupations (Gupta et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Psychological factors, in addition to physical factors, impact occupational performance and participation. Based on three qualitative studies that look at the lived experience of chronic pain, diabetes, and peripheral neuropathy after organ transplant, we know that living with DPN can cause: emotional distress; depression and frustration from decreased participation in meaningful occupations; anxiety and fear; decreased balance confidence; and helplessness (Argoff et al, 2006;Fisher et al, 2007;Textor and Hedrick, 2012). More specifically, participants reported problems with sleep, personal relationships, social activities, work and QoL.…”
Section: Literature Reviewmentioning
confidence: 99%